H∞ Filtering for Cloud-Aided Semi-active Suspension with Delayed Road Information∗. Issue 12 (2015) - Li, Zhaojian; Kolmanovsky, Ilya; Atkins, Ella; Lu, Jianbo; Filev, Dimitar
Abstract: The paper considers a cloud-aided semi-active vehicle suspension. In this system, road profile information is downloaded from a cloud database to facilitate the onboard state estimation. Time-varying delays are considered during the data transmission. An H ∞ filter is designed that exploits both onboard sensor measurements and delayed road profile information from the cloud. Disturbances due to GPS localization error and time delay inaccuracies are treated. The H ∞ performance analysis is presented and sufficient conditions for the existence of the filter are derived as linear matrix inequalities (LMIs). Filter design is then developed with the Projection Lemma. Numerical simulations are presented to illustrate the effectiveness of the designed filter in estimating the suspension states.